PANDANGAN GURU PAMONG TERHADAP PELAKSANAAN PROGRAM PENGALAMAN LAPANGAN (PPL) DI SMP DAN SMA SE GORONTALO - Paramata, Dewi Diana (Jurnal Entropi, 2007)
the Research which entitling View of Teacher of the field experience learning execution program ( PPL) in Yunior and Senior High School in Gorontalo aim to give the input substance like PPL execution pattern to repair the execution PPL for all which concerned, so the PPL execution program that really effective for the forming of teacher candidate and or professional in education, so that this research is expected useful to student of college which will do the activity PPL yet to be unlimber as good as possible in face of PPL execution program and as input to UPT PPL for the repairing of PPL execution program. Method which used is descriptive method. As additional data, use direct interview with headmasters. The Result of research indicate that the View of Teacher of the field experience learning execution program ( PPL) generally is goodness, this is shown by the analysis of data and diagram where the View of Teacher of the field experience learning execution program ( PPL) for every indicator around about: agree, often, and even. So also with the headmaster view that basically the PPL execution program has good and every year it was improvement, but because of change and growth of learning system in school hence oblige the student of college always to follow it so they really prepared to execute PPL.